Symbolic Capital as a Brand Tool of Sociocultural Life (on the Material of the Northern Cities of the Republic of Sakha (Yakutia)) - Khokholova, Irena; Danilova, Natalya; Kysylbaikova, Marina; Pestereva, Kyunney; Vasileva, Alina; Maximova, Daryana; Dyachkovskiy, Semyon (Journal of Education Culture and Society, 2021)
Aim. The aim of the research is to study the symbolic capital of northern cities (semiotic potential) contained in "urban texts" and the influence of the historical memory of a multiethnic region on the political process of the region and the country as a whole, through a comprehensive and interdisciplinary study of the symbolic space of cities in the Republic of Sakha (Yakutia). Methods. The study used the cognitive approach, the method of space-time analysis, and the method of historicism and questionnaire survey. Symbolic space as a text is a heterogeneous content. Results. The results of the study show the importance of a symbolic resource as a brand tool, first, depending on the political context and introduction into the collective memory through a constant "reminder" of its importance and significance in the socio-cultural and everyday life of citizens. The resulting databases of monuments served as the basis for compiling a virtual album of monuments and art objects in the cities of the Republic of Sakha (Yakutia). The research results can practically be applied in the field of education, politics, culture, in the study and promotion of the cultural and historical heritage of the regions of Russia. Conclusions. The urgent problem is the task of preserving the accumulated experience and values, places of memory, relics of the past, as well as ideas about the past that are stored in the memory of its inhabitants and the transfer of this knowledge to the younger generation.